Deciphering the role of autophagy in the immunopathogenesis of inflammatory bowel disease - Li, Yue; Law, Helen Ka Wai (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a typical immune-mediated chronic inflammatory disorder. Following the industrialization and changes in lifestyle, the incidence of IBD in the world is rising, which makes health concerns and heavy burdens all over the world. However, the pathogenesis of IBD remains unclear, and the current understanding of the pathogenesis involves dysregulation of mucosal immunity, gut microbiome dysbiosis, and gut barrier defect based on genetic susceptibility and environmental triggers. In recent years, autophagy has emerged as a key mechanism in IBD development and progression because Genome-Wide Association Study revealed the complex interactions of autophagy in IBD, especially immunopathogenesis. Besides, autophagy markers are also suggested to be potential biomarkers and target treatment in IBD. This review summarizes the autophagy-related genes regulating immune response in IBD. Furthermore, we explore the evolving evidence that autophagy interacts with intestinal epithelial and immune cells to contribute to the inflammatory changes in IBD. Finally, we discuss how novel discovery could further advance our understanding of the role of autophagy and inform novel therapeutic strategies in IBD.